5 GHz laterally-excited bulk-wave resonators (XBARs) based on thin platelets of lithium niobate - Plessky, V; Yandrapalli, S; Turner, P.J; Villanueva, L.G; Koskela, J; Hammond, R.B (Electronics letters, 2019)
In a free-standing 400-nm-thick platelet of crystalline ZY-LiNbO3, narrow electrodes (500 nm) placed periodically with a pitch of a few microns can eXcite standing shear-wave bulk acoustic resonances (XBARs), by utilising lateral electric fields oriented parallel to the crystalline Y-axis and parallel to the plane of the platelet. The resonance frequency of ∼4800 MHz is determined mainly by the platelet thickness and only weakly depends on the electrode width and the pitch. Simulations show quality-factors (Q) at resonance and anti-resonance higher than 1000. Measurements of the first fabricated devices show a resonance Q-factor ∼300, strong piezoelectric coupling ∼25%, (indicated by the large Resonance-antiResonance frequency spacing, ∼11%) and an impedance at resonance of a few ohms. The static capacitance of the devices, corresponds to the imaginary part of the impedance ∼100 Ω. This device opens the possibility for the development of low-loss, wide band, RF filters in the 3–6 GHz range for 4th and 5th generation (4G/5G) mobile phones. XBARs can be produced using standard optical photolithography and MEMS processes. The 3rd, 5th, 7th, and 9th harmonics were observed, up to 38 GHz, and are also promising for high frequency filter design.